Tribological Behaviour of Bonded Solid Lubricant Film in Air and in Vacuum - Changsheng Li; Yoshinori Takeichi; Shinya Shimizu; Masao Uemura; Marian Dzimko; Yuko Tsuya (Communications - Scientific letters of the University of Zilina, 2000)
The friction tests of inorganic bonded composite solid lubricant films (WS2, graphite, BN) were performed in laboratory air and in 10-4 Pa vacuum. The wear traces and transfer films were characterized by scanning electron microscopy (SEM), and Auger electron spectroscopy (AES). Experimental results suggest that when friction tests were conducted in air, graphite plays agoverning role, while in vacuum WS2 plays agoverning role. In case of changing atmosphere from air to vacuum or from vacuum to air, the composite film showed better friction behaviors in vacuum than in air.